2016
DOI: 10.1530/erp-15-0031
|View full text |Cite
|
Sign up to set email alerts
|

Excessive interatrial adiposity is associated with left atrial remodeling, augmented contractile performance in asymptomatic population

Abstract: PurposePericardial adipose tissue had been shown to exert local effects on adjacent cardiac structures. Data regarding the mechanistic link between such measures and left atrial (LA) structural/functional remodeling, a clinical hallmark of early stage heart failure (HF) and atrial fibrillation (AF) incidence, in asymptomatic population remain largely unexplored.MethodsThis retrospective analysis includes 356 subjects free from significant valvular disorders, atrial fibrillation, or clinical HF. Regional adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Similar changes were found in adult patients with interatrial adiposity. These remodeling processes were associated with increased LA global kinetic energy and ejection force at the hemodynamic level, which may serve to compensate for functional LA deterioration in asymptomatic patients [ 10]. It is hoped that these changes are not significant for the lives of our young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes were found in adult patients with interatrial adiposity. These remodeling processes were associated with increased LA global kinetic energy and ejection force at the hemodynamic level, which may serve to compensate for functional LA deterioration in asymptomatic patients [ 10]. It is hoped that these changes are not significant for the lives of our young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a great body of literatures have also demonstrated direct and local negative impacts on myocardial tissue from VAT through elicited oxidative stress and several pathological pro‐inflammatory mechanisms with excessive LA interstitial fibrotic replacement, causing ‘atrial myopathy’ prone to AF onset or perpetuation, 6,13,19,33 leading to HFpEF/AF development 33,34 . Indeed, independent pathological links were observed between abundant epicardial adiposity and structural atrial dilation 35 or subclinical impaired LA mechanics by either speckle‐tracking or MRI assessment 14,36,37 . However, these studies were limited by relatively small number and lack of comprehensive LA measures or follow‐up data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the greater fat depots around the LA in AF patients would be accompanied by a decreased reservoir function through augmented LA kinetic energy and the ejection force. In fact, it has been suggested that regional adipose tissues can be beneficial by preserving myocardial energy supply under certain circumstances, yet simultaneously impose certain negative effects generated by the inflammatory process . Conversely, the maintenance of sinus rhythm after ablation improves the atrial contractile function, and reduces the atrial oxygen consumption and coronary flow.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that regional adipose tissues can be beneficial by preserving myocardial energy supply under certain circumstances, yet simultaneously impose certain negative effects generated by the inflammatory process. 36 Conversely, the maintenance of sinus rhythm after ablation improves the atrial contractile function, and reduces the atrial oxygen consumption and coronary flow. These myocardial conditions would decrease the LA myocardium's energy supply and negative effects of the inflammatory process.…”
Section: Influence Of Eat On Ablation Outcomementioning
confidence: 99%